2020
DOI: 10.1016/j.pdpdt.2020.101908
|View full text |Cite
|
Sign up to set email alerts
|

Visible light plasmon excitation of silver nanoparticles against antibiotic-resistant Pseudomonas aeruginosa

Abstract: The interaction of metallic nanoparticles with light excites a local surface plasmon resonance (LSPR). This phenomenon enables the transfer of hot electrons to substrates that release Reactive Oxygen Species (ROS). In this context, the present study was aimed at enhancing the antibacterial effect of citrate-covered silver nanoparticles (AgNPs), which already possess excellent antimicrobial properties, via LSPR excitation with visible LED against Pseudomonas aeruginosa, one of the most refractory organisms to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 82 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…According to this experiment, it seems that AgNPs, which have antibacterial effects against P. aeruginosa, were enhanced by the formation of ROS via LSPR. Moreover, the release of Ag + occurred several hours after AgNPs had already killed the bacteria [81].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…According to this experiment, it seems that AgNPs, which have antibacterial effects against P. aeruginosa, were enhanced by the formation of ROS via LSPR. Moreover, the release of Ag + occurred several hours after AgNPs had already killed the bacteria [81].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Regarding their antibacterial role, once the AgNPs are in contact with bacteria, the free radical-mediated pore generation into the cell wall is the leading mechanism of bacterial cell death. Therefore, some authors have investigated how to improve the AgNPs' antimicrobial activity via localized surface plasmon resonance (LSPR) to increase the ROS generation by exposure to visible light [80].…”
Section: Silver Npsmentioning
confidence: 99%
“…The main objective of this study was to increase the antibacterial activity of AgNPs by exploiting the capability of LSPR to influence the electronic state of the particles and increase the number of silver ions (Ag + ) which ultimately are responsible for the antimicrobial effect. Recently, research from da Silva and colleagues [80] has shown a link among AgNPs, LSPR, ROS and the AgNPs' antimicrobial activity. The authors claim that, even if some studies support the idea that Ag + plays a main role in antibacterial activity [83], together with the capability of AgNPs to introduce nicks in the cytoplasmic membrane [84], AgNPs and Ag + can also induce ROS formation, which damages the cell cytoskeleton, oxidizing nucleic acids and proteins, leading to potential chromosomal aberrations and cell death [85].…”
Section: Silver Npsmentioning
confidence: 99%
“…However, the ROS-mediated cytotoxicity was more evident in the case of Gram-negative bacterium [181]. Light-irradiated enhanced bactericidal effects were also reported for P. aeruginosa treated with citrate-coated nanoparticles [182].…”
Section: Silver Nanoparticles For Antibacterial Applicationsmentioning
confidence: 76%